2022
DOI: 10.1111/jfbc.14472
|View full text |Cite
|
Sign up to set email alerts
|

Amazonian fruits with potential effects on COVID‐19 by inflammaging modulation: A narrative review

Abstract: The COVID‐19 pandemic had a great impact on the mortality of older adults and, chronic non‐ transmissible diseases (CNTDs) patients, likely previous inflammaging condition that is common in these subjects. It is possible that functional foods could attenuate viral infection conditions such as SARS‐CoV‐2 (severe acute respiratory syndrome coronavirus 2), the causal agent of COVID‐19 pandemic. Previous evidence suggested that some fruits consumed by Amazonian Diet from Pre‐Colombian times could present relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…Substantial research has been conducted on the impact of the pandemic on food consumption in European countries such as Italy (Di Renzo et al, 2020;Fanelli, 2021;Caso et al, 2022), Spain (Batlle-Bayer et al, 2020), Poland (Sidor and Rzymski, 2020), Turkey (Kaya et al, 2021), and in American countries like Brazil (Ferreira Rodrigues et al, 2021;Manica-Cattani et al, 2022), United States (Chenarides et al, 2021;Parekh et al, 2021), as well as Asian nations such as Qatar (Ben Hassen et al, 2020), Japan , India (Jaacks et al, 2021), Iran (Mohajeri et al, 2021) and Bangladesh (Akter et al, 2022). All these provide important basis for this paper.…”
Section: Forest Food Related Researchmentioning
confidence: 99%
“…Substantial research has been conducted on the impact of the pandemic on food consumption in European countries such as Italy (Di Renzo et al, 2020;Fanelli, 2021;Caso et al, 2022), Spain (Batlle-Bayer et al, 2020), Poland (Sidor and Rzymski, 2020), Turkey (Kaya et al, 2021), and in American countries like Brazil (Ferreira Rodrigues et al, 2021;Manica-Cattani et al, 2022), United States (Chenarides et al, 2021;Parekh et al, 2021), as well as Asian nations such as Qatar (Ben Hassen et al, 2020), Japan , India (Jaacks et al, 2021), Iran (Mohajeri et al, 2021) and Bangladesh (Akter et al, 2022). All these provide important basis for this paper.…”
Section: Forest Food Related Researchmentioning
confidence: 99%
“…Two narrative reviews discussed the impact of including fresh fruits and vegetables on specific inflammatory factors related to respiratory diseases and COVID-19. 27,28 Both reviews completed systematic literature searches on key terms. One included experimental, epidemiological, and clinical data and the other did not specify data type.…”
Section: Fresh Fruits and Vegetablesmentioning
confidence: 99%
“…One study cited a reduction in plasma levels of interferon-gamma (IFN-γ) with regular consumption of Acai juice in subjects with metabolic syndrome. 28 Both of these reviews suggested the relationship between antioxidant content in Amazonian fruits 28 and fresh fruits and vegetables 27 and improving immune system function. However, neither study provided data directly related to COVID-19 risk or severity of symptoms.…”
Section: Fresh Fruits and Vegetablesmentioning
confidence: 99%
“…Therefore, the use of foods with antioxidant action and phytochemical protectors may be relevant for the prevention of diseases related to increased oxidative stress [ 27 ]. It is also noteworthy that Amazonian fruits have not only demonstrated potential in the prevention and control of chronic diseases, but also have an interesting applicability in the realm of infectious diseases, such as COVID-19, responsible for the greatest health crisis in recent history of humanity [ 28 ]. The immunomodulatory, antioxidant, and anti-inflammatory actions of these fruits have already been demonstrated [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also noteworthy that Amazonian fruits have not only demonstrated potential in the prevention and control of chronic diseases, but also have an interesting applicability in the realm of infectious diseases, such as COVID-19, responsible for the greatest health crisis in recent history of humanity [ 28 ]. The immunomodulatory, antioxidant, and anti-inflammatory actions of these fruits have already been demonstrated [ 28 , 29 ]. The potential utility of these fruits against the sequelae of infectious diseases becomes especially important in countries such as Brazil, where these diseases have great epidemiological relevance.…”
Section: Introductionmentioning
confidence: 99%